Using Pseudomonas aeruginosa PAO1 to evaluate hydrogen peroxide as a biofouling control agent in membrane treatment systems. (2nd November 2016) - Yang, Y.; Kitajima, M.; Pham, T.P.T.; Yu, L.; Ling, R.; Gin, K.Y.H.; Reinhard, M.
Abstract: Hydrogen peroxide (H2 O2 ) is widely used in water treatment for biofouling control and, in conjunction with catalysts, as a powerful oxidant for contaminant destruction. H2 O2 could potentially serve as an antifouling agent in reverse osmosis systems in lieu of chlorine‐based disinfectants. The dependence of the biocidal efficiency of H2 O2 on cell density, temperature and H2 O2 concentration by determining the growth, attachment and viability of the model bacterium Pseudomonas aeruginosa PAO1 was studied. For controlling growth of planktonic PAO1 cells, the minimally required H2 O2 concentration depends on the cell density and temperature. The effect of H2 O2 to remove the existing biofilm was found to be effective in the presence of a high concentration bicarbonate (8·4 g l −1 ), which forms peroxymonocarbonate, a strong oxidant and disinfectant. Treatment with H2 O2 –bicarbonate reduced the density of live PAO1 cells, removed extracellular polymeric substances and lowered the average biofilm thickness while maintaining the integrity of the membrane, suggesting that this type of treatment may be a suitable 'in‐place‐cleaning' procedure for biofouled membranes. Significance and Impact of the Study: H2 O2 is evaluated as a potential replacement for chlorine to control biofouling in membrane‐based water treatment systems. The biocidal efficacy of H2 O2 was evaluated as a function of H2 O2 concentration, cell density and temperature using the model organism Pseudomonas aeruginosa PAO1. Results demonstrated that at low temperatures and low cell densities, bacterial growth and membrane biofouling can be prevented by low H2 O2 concentrations, and existing biofilms could be removed by H2 O2 –bicarbonate mixtures. Findings suggested that H2 O2 could be used as a low cost agent for prevention and controlling biofouling in reverse osmosis applications. Abstract : Significance and Impact of the Study: H2 O2 is evaluated as a potential replacement for chlorine to control biofouling in membrane‐based water treatment systems. The biocidal efficacy of H2 O2 was evaluated as a function of H2 O2 concentration, cell density and temperature using the model organism Pseudomonas aeruginosa PAO1. Results demonstrated that at low temperatures and low cell densities, bacterial growth and membrane biofouling can be prevented by low H2 O2 concentrations, and existing biofilms could be removed by H2 O2 –bicarbonate mixtures. Findings suggested that H2 O2 could be used as a low cost agent for prevention and controlling biofouling in reverse osmosis applications.